2009
DOI: 10.2298/vsp0912998o
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intracoronary injections of bone-marrow-derived mononuclear cells on large myocardial infarction outcome: Quantum of initial necrosis is the key

Abstract: In the patients with first large STEMI intracoronary injection of autologous bone-marrow-derived MNC leads to the significant decrease of myocardial infarction size but not the significant improvement of LVEF after four months. Higher serum LDH levels after STEMI and very large baseline infarction size are predictors of failure of stem cell therapy in our group of STEMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 12 publications
0
16
0
7
Order By: Relevance
“…Most studies were conducted in patients with acute MI and intracoronary application of BMMNC (about 30 randomized trials) and demonstrated conflicting results [21][22][23][24][25][26] . On the other hand, 12 studies reporting inconsistent results were performed in the patients with chronic ischemic cardiomyopathy, among them several with intramyocardial implantation concomitant to CABG 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were conducted in patients with acute MI and intracoronary application of BMMNC (about 30 randomized trials) and demonstrated conflicting results [21][22][23][24][25][26] . On the other hand, 12 studies reporting inconsistent results were performed in the patients with chronic ischemic cardiomyopathy, among them several with intramyocardial implantation concomitant to CABG 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the three largest clinical BMC trials (Lunde et al, 2006; Meluzín et al, 2006; Schachinger et al, 2006b), only REPAIR-AMI trial indicated that baseline EF correlated with EF change ( p  = 0.04) but the statistical analysis did not taken autocorrelation of the parameters into account, which should be considered as a major limitation. However, recent observations from small studies showed that large infarcts were less likely to get benefit from BMC therapy (Obradović et al, 2009; Traverse et al, 2010). Global LV function was quite preserved in our patient population, potentially improving the likelihood of a positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers began to realize that manipulation of adult animal tissues could sometimes yield previously unsuspected cell types; for example, that some BM derived SCs could be turned into cardiomyocytes, hepatocytes or nerve and other somatic cells -phenomenon known as the SC "plasticity". Finally, using SC plasticity, cell-based therapies for treatment of the ischemic heart diseases started through beginning of the new millennium and currently are in an expansion phase in the other fields of regenerative medicine [21][22][23][24][25][26][27][28][29][30].…”
Section: Stem Cell Transplants -A Short Chronological Considerationmentioning
confidence: 99%
“…We have also investigated SC-harvesting protocols with optimized cell source, collection timepoint and processed blood volume, CD34-threshold dose (calculed by ideal body mass), as well as immature (CD34 + /CD33 -, CD34 + /CD38 -, CD34 + /DR -, CD34 + /CD90 + ) vs. mature (CD34 + / CD33 + , CD34 + /CD38 + , CD34 + /DR + , CD34 + /CD90 -) CD34-subset ratio in harvest [8,26,28,50].…”
Section: Conventional Stem Cell Transplants -A Synopsis Of the Clinicmentioning
confidence: 99%
See 1 more Smart Citation